Confluence and affluence in design ambiguity scales - Costa, Carlos Casimiro da (2013)
Full Paper Acceptance and Publishing Certificate Awarded to Carlos Casimiro da Costa Jacinta Helena Alves Lourenço Casimiro da Costa For the acceptance and publication of the paper “Confluence and affluence in Design ambiguity scales”, in the context of the Cumulus Conference “Projecting Design 2012: Global Design Bridge”, organized by Cumulus Association, Aalto University and DuocUC.